Differences in time to task failure and fatigability between children and young adults: A systematic review and meta-analysis - Souron, Robin; Carayol, Marion; Martin, Vincent; Piponnier, Enzo; Duché, Pascale; Gruet, Mathieu (Frontiers in Physiology, 2022)
The transition from childhood to adulthood is characterized by many physiological processes impacting exercise performance. Performance fatigability and time to task failure are commonly used to capture exercise performance. This review aimed to determine the differences in fatigability and TTF between youth (including both children and adolescents) and young adults, and to evaluate the influence of exercise modalities (i.e. exercise duration and type of exercise) on these differences. Medline, SPORTDiscus and Cochrane Library were searched. Thirty-four studies were included. The meta-analyses revealed that both children (SMD –1.15; p < 0.001) and adolescents (SMD –1.26; p = 0.022) were less fatigable than adults. Additional analysis revealed that children were less fatigable during dynamic exercises (SMD –1.58; p < 0.001) with no differences during isometric ones (SMD –0.46; p = 0.22). Children (SMD 0.89; p = 0.018) but not adolescents (SMD 0.75; p = 0.090) had longer TTF than adults. Additional analyses revealed i) that children had longer TTF for isometric (SMD 1.25; p < 0.001) but not dynamic exercises (SMD –0.27; p = 0.83), and ii) that TTF differences between children and adults were larger for short- (SMD 1.46; p = 0.028) than long-duration exercises (SMD 0.20; p = 0.64). Children have higher endurance and are less fatigable than adults. These differences are influenced by the exercise modality, suggesting distinct physiological functioning during exercise between children and adults. The low number of studies comparing these outcomes between adolescents and adults prevents robust conclusions and warrants further investigations in this specific population.